Idiopathic orbital inflammatory pseudotumour mimicking optic nerve sheath meningioma- a case report. - Umi Kalthum MN,; Amin A,; Syazarina SO,; Faridah HA, (Department of Surgery, UKM Medical Centre, 2013)
A 42-year-old Malay gentleman presented with progressive painless blurring of vision on his left eye associated with ocular ache, redness and increasing proptosis. Examination revealed presence of relative afferent papillary defect with visual acuity of counting finger, and 6/6 on the right eye. Extraocular muscle movement of the left eye was restricted to ten percent in all directions. Computed tomography (CT) and magnetic resonance imaging (MRI) showed enhancing mass occupying the left orbital apex. Diagnosis of optic nerve sheath meningioma was made, and patient subsequently went for radiotherapy. His symptoms subsided completely, until he presented with similar visual complains, and fullness of the upper lid two years later. A repeated MRI showed enlargement of superior and lateral recti muscles with extension to lacrimal gland region. Biopsy of the lacrimal gland revealed inflammatory cells consistent of inflammatory pseudotumor. High dose systemic steroid was instituted, followed by slow tapering of oral steroid. His symptoms completely resolved, and latest visual acuity was 6/9, with no recurrence, to date.